Nearwork‐induced transient myopia (NITM) in anisometropia. (12th May 2013) - Lin, Zhong; Vasudevan, Balamurali; Liang, Yuan Bo; Zhang, Yi Cao; Zhao, Shi Qiang; Yang, Xiao Dong; Wang, Ning Li; Gilmartin, Bernard; Ciuffreda, Kenneth J
Abstract Objective To assess the magnitude of nearwork‐induced transient myopia (NITM) under binocular viewing conditions separately in each eye of individuals with mild to moderate anisometropia to determine the relationship between NITM and their interocular refractive error. Methods Forty‐three children and young adults with anisometropia [cycloplegic spherical equivalent (SE) difference >1.00 D] were tested (ages 9–28 years). NITM was measured with binocular viewing separately in each eye after binocularly performing a sustained near task (5 D) for 5 min incorporating a cognitive demand using an open‐field, infrared autorefractor (Grand‐Seiko, WAM‐5500). Data were averaged over 10 s bins for 3 min in each eye. Initial NITM, its decay time (DT), and its decay area (DA) were determined. A‐scan ultrasound ocular biometry was also performed to determine the axial length of each eye. Results The more myopic eye exhibited increased initial NITM, DT, and DA as compared to the less myopic eye (0.21 ± 0.16 D vs 0.15 ± 0.13 D, p = 0.026; 108.4 ± 64.3 secs vs 87.0 ± 65.2 secs, p = 0.04; and 17.6 ± 18.7 D*secs vs 12.3 ± 15.7 D*secs, p = 0.064), respectively. The difference in DA and the difference in SE between the more versus less myopic eye were significantly correlated (r = 0.31, p = 0.044). Furthermore, 63% (27/43), 56% (24/43), and 70% (30/43) of the more myopic eyes exhibited increased initial NITM, longer DT, and larger DA, respectively, than found in the less myopic eye. Conclusions In approximately two‐thirds of the anisometropic individuals, the initial NITM and its decay area were significantly increased in the more myopic eye as compared to the less myopic eye. NITM may play an important role in the development of interocular differences in myopia, although a causal relationship is yet to be established. Furthermore, the findings have potentially important implications regarding accommodative control and interocular accommodative responsitivity in anisometropia, in particular for anisomyopia.